The First Maritime Charters of the Petrine Epoch: Translations and Adaptation - Irina Voznesenskaya; Georgiy Molkov (Studi Slavistici)
The article examines the development of the text of the maritime charters in the late 17th – early 18th centuries Russia. New sources have made it possible to establish that there were at least four different translations of the Dutch charter. An analysis of the maritime terminology presented in different translations of the charter showed that for translators the vocabulary of the Dutch original was not yet decisive for this period. Even when the Dutch word was borrowed into the Russian language at the end of the 17th century to translate it, a synonymous term of non-Dutch origin could be used in the charter. The lack of stable usage in this area is clearly demonstrated by examples of translating the same concepts in individual ways in each of the four translations. Most of the traditional Russian terms are presented in the earliest translation of 1692. The use of borrowings in later translations could be influenced by both Dutch and English maritime vocabulary. Some of these terms show signs of borrowing through the oral environment.